Analysis of mechanical behaviour of 3D printed polylactic acid – polycarbonate-urethane for articular cartilage material - Kazim, Muhammad Nur Akmal (2024)
Polylactic acid (PLA) and polycarbonate urethane (PCU) are widely utilized materials in the medical field, particularly for articular cartilage applications. These materials exhibit remarkable strength, durability, and high wear resistance. However, the current artificial implants made lack of porous properties required for optimal lubrication. Thus, the purpose of this study is to analyse the mechanical behaviour of 3D printed polylactic acid – polycarbonate urethane for artificial cartilage material. A polymer blend of PLA-PCU with the composition of 90% PLA and 10% PCU was extruded using twin-screw extruder. The Fused Filament Fabrication (FFF) technology was employed to print the specimen. Subsequently, the response surface methodology was utilized to analyse the experimental data and develop an effective empirical prediction model. A hardness test using a Shore D durometer and a compression test using Instron UTM5 were carried out. The study's results showed that the generated model was not significantly related to the absorption rate but was highly significant for the surface roughness response parameter. Detailed analysis of the results revealed that layer thickness was the most significant factor affecting surface roughness where higher layer thickness produced higher surface roughness, while PCU composition affected absorption rate. The optimal printing process parameters for achieving the desired surface roughness (2.5400 µm) and absorption rate (0.0470%) were obtained by setting the PCU concentration to 10 wt.%, layer thickness to 0.1 mm, nozzle speed to 15 mm/s, and extruding temperature to 195℃. The study results demonstrated that the addition of PCU to PLA reduced the hardness level of the specimens. Interestingly, specimens with the same element exhibited almost the same hardness level despite being fabricated using different layer thicknesses. Moreover, the results have shown that compared to 3D-printed PLA, adding PCU to PLA reduced the compressive strength and Young's modulus of the 3D-printed polymer blend. The thickness of the printing layers has an impact on the mechanical characteristics of 3D-printed specimens as well as specimen with lower layer thickness is stronger and stiffer. It has also been found that higher layer thickness resulting higher hardness-to-elasticity ratio, which is an essential factor for proper load transfer. The cross-sectional surface area of the compression-moulded specimen is smoother than that of the 3D-printed specimen, which contributes to distinct sorts of failure modes for both specimens, according to the SEM image analysis. These findings suggest that PLA-PCU composite materials could be a suitable option for medical applications that require high wear resistance, strength, and durability.